1991
DOI: 10.1111/j.1471-4159.1991.tb08197.x
|View full text |Cite
|
Sign up to set email alerts
|

Regulation by Interleukin‐1 of Nerve Growth Factor Secretion and Nerve Growth Factor mRNA Expression in Rat Primary Astroglial Cultures

Abstract: Primary cultures of neonatal rat cortical astrocytes contain low cellular levels (about 2 pg/mg of protein) of nerve growth factor (NGF), but secrete significant amounts of NGF into the culture medium (about 540 pg of NGF/mg of cell protein/38-h incubation). Incubation of astrocytes with interleukin-1 (IL-1) increased the cellular content of NGF and the amount secreted by about threefold. In comparison, cerebellar astrocytes secreted significant amounts of NGF, and the secretion was also stimulated by IL-1. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
54
0
1

Year Published

1993
1993
2009
2009

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 145 publications
(56 citation statements)
references
References 43 publications
1
54
0
1
Order By: Relevance
“…IL-1␤ is widely recognized for its ability to regulate the expression of many different molecules involved in determining neuronal death (59). IL-1␤ may also induce the release of neurotropins (60), but it can also initiate the production of toxic reactive oxygen species, such as NO, through the induction of iNOS (61). Of interest, U373 cells exhibited greater reactivity than primary astrocytes in response to thrombin and TF, especially for IL-1␤, which probably reflected residual effects of thrombin in serum and the need to culture primary astrocytes in high levels of serum for survival before experimental use.…”
Section: Discussionmentioning
confidence: 99%
“…IL-1␤ is widely recognized for its ability to regulate the expression of many different molecules involved in determining neuronal death (59). IL-1␤ may also induce the release of neurotropins (60), but it can also initiate the production of toxic reactive oxygen species, such as NO, through the induction of iNOS (61). Of interest, U373 cells exhibited greater reactivity than primary astrocytes in response to thrombin and TF, especially for IL-1␤, which probably reflected residual effects of thrombin in serum and the need to culture primary astrocytes in high levels of serum for survival before experimental use.…”
Section: Discussionmentioning
confidence: 99%
“…Cytokine activation of astrocytes also induces elevated levels of nerve growth factor (NGF) expression (6,7,8). NGF is a member of a family of neurotrophic factors, called neurotrophins, which includes brain-derived neurotrophic factor (BDNF), neurotrophin-3 (NT-3), and neurotrophin-4/5 (NT-4/ 5).…”
mentioning
confidence: 99%
“…In contrast, its staining was strong and widely distributed around the arteries and in the PALS of SCID mice, suggesting that its production is usually inhibited by the immune system in normal animals. IL-1␤ is known to stimulate NGF production in fibroblasts, astrocytes, and other cell types (34,35), and we reported that it promoted sympathetic neurite outgrowth in lymphoid tissues by stimulating NGF production, using a rodent sympathetic ganglion and lymphoid tissue explant coculture system (11,12). Because IL-1␤ levels were found to be higher in SCID mice, it may have been responsible, at least in part, for the elevated levels of NGF in the spleen of these animals.…”
Section: Discussionmentioning
confidence: 99%